Do the importations of crop products affect the genetic diversity from landraces? A study case in garlic (Allium sativum L.) - Gomes Viana J.P. (2021)
© 2020, Springer Nature B.V.The increase in importations of elite garlic (Allium sativum L.) in Brazil to meet the local demand in many cities may affect the cultivation of garlic landraces in small family farming systems by driving to the reduction of the harvested area and genetic diversity. The landraces are fundamental sources of genetic variability and adapted germplasm that could be potentially be implemented in breeding programs. The objective of this study was to evaluate the changes in the patterns of genetic diversity in landraces cultivated in family farming systems after three decades of competitiveness with imported garlic. Three landraces of garlic currently cultivated on family farms in the Picos municipality and immediate regions (7° 04′ 55.5″ S 41° 28′ 04.2″ W) and a landrace collected in the same region in the 1970s, before the increase of imports of garlic in Brazil, were selected for this study. Additionally, six garlic accessions from the Garlic Germplasm Bank from ESALQ/USP (Sao Paulo—Brazil) were selected to parallel the genetic diversity present in landraces with other varieties collected in Brazil, completing a set of ten accessions. A randomized block design was used to evaluate nine agro-morphological traits and rank the landraces according to the economically important agronomic traits. The potential changes in genetic diversity patterns and population structure in these populations were also evaluated at a molecular level using eight microsatellite markers. The agro-morphological evaluation indicates that there is genetic diversity in the garlic populations, and it is structured between Picos landraces and ESALQ/USP accessions. There is also evidence of genetic structure between the landraces and populations of the ESALQ/USP accessions (K = 3) based on a Bayesian clustering approach. The moderate genetic differentiation (FST = 0.09) accessed by the microsatellite markers may be associated with the existence of these two different gene pools: Picos landraces and ESALQ/USP accessions. The results indicate that the reduction in harvested areas in the past decades did not affect most morphological characteristics in the landraces, but there was a reduction in the quality of the bulbs. The garlic landraces cultivated nowadays in Picos municipality present a higher number of cloves per bulb, an undesirable characteristic that may affect its commercial value. However, we demonstrate that even with such reduction in harvested areas due to the lack of competitiveness of landraces, there was no reduction in the molecular genetic diversity in these landraces accessed by the microsatellite markers. These are promising results since there is genetic diversity to implement these landraces in genetic breeding programs.